KAMPANYE LGBT DI MEDIA SOSIAL FACEBOOK DAN WHATSAPP - Reni Juliani (Universitas Teuku Umar, 2018)
Indonesia is a country where all religious leaders reject LGBT behavior. Due to the uncertainty about the fate of their existence, LGBT people are increasingly aggressively advocating for legal protection and LGBT legalization in Indonesia. Internet campaigns are mostly chosen by LGBT people as a media campaign for them. This can be seen from the rise of social media used by the Indonesian people, especially Facebook and Whatsapp. Based on the phenomenom described above, the researcher is trying to figure out how the campaigns are being conducted by LGBT people on Facebook and Whatsapp. This study used a library research method where the results showed that Facebook and Whatsapp were indeed social media followers of the LGBT campaign. Facebook and Whatsapp have their own LGBT group. The Facebook and Whatsapp chat pages also include emo, stickers and gifs with LGBT symbols such as rainbow colors, pride, gay words and other words and illustrations that lead to LGBT. Keywords: Campaign, LGBT, Facebook, Whatsapp.